(Morpho)syntactic Variation in Agreement: Specificational Copular Clauses Across Germanic - Hartmann, Jutta M.; Heycock, Caroline (Frontiers in Psychology, 2020)
In this paper we bring together the results of our research into agreement in copular clauses in 4 four different Germanic languages—Dutch, German, Faroese, Icelandic—in order to provide an 5 overview of the results. These cases present a particularly interesting window into how verbal 6 agreement operates, since there are two potential controllers of agreement, which may disagree 7 in person and/or number (The source of the rumour BE the neighbours / you-SG / you-PL). We 8 will show that there is variation at all levels in which nominal controls agreement: cross-linguistic, 9 inter-speaker within a single language, and intra-speaker. We argue that our data support the 10 following claims: (1) “Downward” agreement for person, as well as number, with a nominal that is 11 not in the canonical subject position is possible and in some cases preferred; (2) The agreement 12 patterns observed in Icelandic and Faroese support the hypothesis that in these languages there 13 are distinct Number and Person heads; (3) “Downward” agreement from a high position in the 14 left-periphery is a grammatically distinct phenomenon from agreement when the verb remains 15 in a lower position in the clause; (4) In some languages and some configurations, speakers 16 show a significant degree of indeterminacy in their judgments and production suggesting that 17 speakers use more than one grammar. We relate our findings to current discussions in the 18 generative literature on subject agreement and in particular differences between number and 19 person agreement, and possible connections to restrictions on object clitics, and we also discuss 20 questions that remain open, and invite new, cross-disciplinary research.